2020
DOI: 10.1159/000506900
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Global Developmental Delay: A Retrospective Study

Abstract: Introduction: Global developmental delay (GDD) is defined as a significant delay in one or more developmental domains. Aims and Objectives: To study the prevalence of normal and abnormal magnetic resonance imaging (MRI) in pediatric patients presenting with GDD, and how abnormal MRI helps in the diagnosis of children with GDD. Materials and Methods: This was a retrospective observational study conducted at the King Fahad Specialist Hospital Dammam. MRI of the brain was conducted on 170 patients who were referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…ALOX5 also demonstrated a rapid increase in expression from the infancy stage till the end of adolescence in the cerebellar cortex, which controls the physical motors [ 83 ] ( Figure 5 b). Previous studies have shown that the abnormalities in the neocortex and cerebellar cortex could contribute to the phenotype and pathogenesis of developmental delay [ 84 , 85 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALOX5 also demonstrated a rapid increase in expression from the infancy stage till the end of adolescence in the cerebellar cortex, which controls the physical motors [ 83 ] ( Figure 5 b). Previous studies have shown that the abnormalities in the neocortex and cerebellar cortex could contribute to the phenotype and pathogenesis of developmental delay [ 84 , 85 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALOX5 also demonstrated a rapid increase in expression from the infancy stage till the end of adolescence in the cerebellar cortex, which controls the physical motors [77] (Figure .5b). Previous studies have shown that the abnormalities in the neocortex and cerebellar cortex could contribute to the phenotype and pathogenesis of developmental delay [78][79][80][81].…”
Section: Identification Of New Potential Dd Genes and De Novo Mutationsmentioning
confidence: 99%
“…The protocols used are Axial DWI, TSE T1W, TSE T2W, FLAIR, PD, T2TIRM, coronal T1TIR, and T2 TSE and sagittal T1 TSE. [51] For initial screening, these protocols can be used but should be modified according to the findings. For example, if there is hydrocephalus or leukodystrophy, then appropriate additional sequences should be added.…”
Section: Indicationsmentioning
confidence: 99%